Development and validation of a patient-reported outcome measure for systemic sclerosis: the EULAR Systemic Sclerosis Impact of Disease (ScleroID) questionnaire. Issue 4 (25th November 2021) - Becker, Mike O; Dobrota, Rucsandra; Garaiman, Alexandru; Debelak, Rudolf; Fligelstone, Kim; Tyrrell Kennedy, Ann; Roennow, Annelise; Allanore, Yannick; Carreira, Patricia E; Czirják, László; Denton, Christopher P; Hesselstrand, Roger; et al.
Abstract : Objectives: Patient-reported outcome measures (PROMs) are important for clinical practice and research. Given the high unmet need, our aim was to develop a comprehensive PROM for systemic sclerosis (SSc), jointly with patient experts. Methods: This European Alliance of Associations for Rheumatology (EULAR)-endorsed project involved 11 European SSc centres. Relevant health dimensions were chosen and prioritised by patients. The resulting Systemic Sclerosis Impact of Disease (ScleroID) questionnaire was subsequently weighted and validated by Outcome Measures in Rheumatology criteria in an observational cohort study, cross-sectionally and longitudinally. As comparators, SSc-Health Assessment Questionnaire (HAQ), EuroQol Five Dimensional (EQ-5D), Short Form-36 (SF-36) were included. Results: Initially, 17 health dimensions were selected and prioritised. The top 10 health dimensions were selected for the ScleroID questionnaire. Importantly, Raynaud's phenomenon, impaired hand function, pain and fatigue had the highest patient-reported disease impact. The validation cohort study included 472 patients with a baseline visit, from which 109 had a test–retest reliability visit and 113 had a follow-up visit (85% female, 38% diffuse SSc, mean age 58 years, mean disease duration 9 years). The total ScleroID score showed strong Pearson correlation coefficients with comparators (SSc-HAQ, 0.73; Patient's global assessment, Visual Analogue Scale 0.77; HAQ-Disability Index, 0.62; SF-36 physical score, −0.62; each p<0.001). The internal consistency was strong: Cronbach's alpha was 0.87, similar to SSc-HAQ (0.88) and higher than EQ-5D (0.77). The ScleroID had excellent reliability and good sensitivity to change, superior to all comparators (intraclass correlation coefficient 0.84; standardised response mean 0.57). Conclusions: We have developed and validated the EULAR ScleroID, which is a novel, brief, disease-specific, patient-derived, disease impact PROM, suitable for research and clinical use in SSc.